The role of natural plants with incorporation of tocopherols, ubiquinone and tocotrienols in nanoemulsion formulation: a mini review / Noreen Ang Azlan and Vitalis Ronald Eden - Ang Azlan, Noreen; Eden, Vitalis Ronald (Faculty of Pharmacy, 2024)
Natural oils and fatty acids are frequently employed as key components in nanoemulsion formulations to enhance permeability in various pharmaceutical and cosmetic products. Their inclusion contributes to the formulation's ability to improve the absorption and bioavailability of active ingredients. The use of these natural oils and fatty acids in nanoemulsions is valued for their compatibility with biological systems, providing a versatile and effective means to enhance the delivery. The natural plant-based derivatives in nanoemulsion are favoured due to their safety, efficacy, and cost-effectiveness with potential therapeutic benefits. Furthermore, incorporating natural oils and fatty acids into nanoemulsion enhances the absorption rate of bioactive content, thereby amplifying their effectiveness. Combining both tocotrienols and ubiquinone in nanoemulsions is a common practice as potent antioxidants and stabilizers in formulations. Furthermore, it may enhance the permeability of active ingredients by facilitating their absorption and bioavailability. This integration represents a highly promising strategy for the foreseeable future. Meanwhile, the interest of nanotechnology has grown significantly, as evidenced by the growing number of publications in this field. This innovative technology holds the potential for long-term viability in cosmetic formulations, offering businesses the opportunity to stay relevant by providing consumers with cutting-edge and effective cosmeceutical products.